The Community College Presidents’ Initiative in Science, Technology, Engineering, and Mathematics - George Boggs (Educational Considerations, 2025)
The nation’s community colleges play a key role in addressing the need to expand and diversify the STEM technological workforce. However, significant barriers must be overcome for the programs to meet the increasing demand for skilled employees. The programs are expensive to establish and maintain; community colleges are generally underfunded; faculty, staff, and administrators are often not experienced in raising external funding or establishing partnerships with business and industry; and, most community colleges are small institutions without grants offices or staff experienced in preparing grant proposals. The Community College Presidents’ Initiative in Science, Technology, Engineering, and Mathematics (CCPI-STEM) is a multifaceted project, funded by the Advanced Technological Education (ATE) Program at the National Science Foundation (NSF), intended to inform community college leaders and aspiring leaders about the importance of STEM workforce challenges and to assist them and their faculty and staff in securing grant funding and implementing needed programs. This manuscript will provide an overview of CCPI-STEM.
Keywords: Community College Presidents’ Initiative; STEM